Models of Renal Cell Carcinoma Used to Investigate Molecular Mechanisms and Develop New Therapeutics - Shapiro, Daniel D.; Virumbrales-Muñoz, Maria; Beebe, David J.; Abel, E. Jason (Frontiers in Oncology, 2022)
Modeling renal cell carcinoma is critical to investigating tumor biology and therapeutic mechanisms. Multiple systems have been developed to represent critical components of the tumor and its surrounding microenvironment. Prominent in vitro models include traditional cell cultures, 3D organoid models, and microphysiological devices. In vivo models consist of murine patient derived xenografts or genetically engineered xenografts. Each system has unique advantages as well as limitations and researchers must thoroughly understand each model to properly investigate research questions. This review addresses common model systems for renal cell carcinoma and critically evaluates their performance and ability to measure tumor characteristics.